Harnessing internal communities: The role of boundary structures - Crespin-Mazet, Florence; Dupouët, Olivier; Goglio, Karine; Neukam, Marion (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
Relying on two case studies, this paper investigates how new knowledge produced by internal communities is integrated in the hosting firms’ activities and procedures. Its main contribution highlights the key role played by boundary structures lying at the interface between communities and the managerial strata of the organization. These structures are instrumental in the boundary work underpinning integration: aligning the communities’ outputs with the firms’ strategy and negotiating their acceptance by top managers. Their role goes beyond a mere diffusion process and includes combining and adapting the managerial and communitarian logics while preserving the autonomy and internal functioning of communities. Due to their collective character, this integration mechanism differs from the sponsor-leader dyad found in the literature on communities.